The association between the genetic structures of commonly incompatible plasmids in Gram-negative bacteria, their distribution and the resistance genes - Lei Fang; Ruyan Chen; Chenyu Li; Jingjing Sun; Ruishan Liu; Yanhao Shen; Xiaobing Guo (Frontiers in Cellular and Infection Microbiology)
Incompatible plasmids play a crucial role in the horizontal transfer of antibiotic resistance in bacteria, particularly in Gram-negative bacteria, and have thus attracted considerable attention in the field of microbiological research. In the 1970s, these plasmids, housing an array of resistance genes and genetic elements, were predominantly discovered. They exhibit a broad presence in diverse host bacteria, showcasing diversity in geographic distribution and the spectrum of antibiotic resistance genes. The complex genetic structure of plasmids further accelerates the accumulation of resistance genes in Gram-negative bacteria. This article offers a comprehensive review encompassing the discovery process, host distribution, geographic prevalence, carried resistance genes, and the genetic structure of different types incompatible plasmids, including IncA, IncC, IncF, IncL, IncM, IncH, and IncP. It serves as a valuable reference for enhancing our understanding of the role of these different types of plasmids in bacterial evolution and the dissemination of antibiotic resistance.